Making Film Programmes for the Bbc and Channel 4: The Shift From In-House ‘Producer Unit’ to Independent ‘Package-Unit’ Production. - Kerr, Paul (Historical Journal of Film, Radio & Television, 2013)
This article examines the shift in British television programming from vertically integrated, in-house BBC producer-unit production to commissioned-out, independent, package-unit production typified by Channel 4. This shift is characteristic of much British TV production but has rarely been experienced within the same series and by largely the same production team. The article analyses that shift as it impinged on two specific series, both film magazine programmes that I was personally involved in producing. The first,Moving Pictures(BBC2, 1990–1996), moved from in-house to independent production between its first and second series, though I remained as Series Editor. The second,Kiss Kiss Bang Bang(Channel 4, 1998), was made by the same independent production company and several of the same programme-makers (I was Executive Producer) but for Channel 4 rather than the BBC. Whilst much has been written about the economic and employment consequences of independent production, there has been little attempt to investigate whether that shift had any consequences on programming. By analysing two specific series and adapting Janet Staiger’s pioneering discussion of Hollywood independents in the 1950s, this article suggests how that shift helped transform the forms and formats of contemporary British television.